ENHANCING CRITICAL READING SKILLS THROUGH ORGANIZED LEARNING USING THE SQ5R TEACHING METHOD : A CASE STUDY OF STUDENTS AT BANGKOK THONBURI UNIVERSITY - Deelert, Wirawan; Wiyaporn, Suthasinee (Journal of MCU Nakhondhat, 2024)
The objectives of this research were to 1) compare the critical reading abilities of first-year students before and after organized learning using the SQ5R teaching method, and 2) investigate the opinions of first - year students regarding SQ5R teaching method. The study focused on a sample group of first-year students enrolled in the course GT 105 Thai Language for Career during the first semester of the academic year 2023, totaling 55 students. The research employed a sampling method based on Krejcie and Morgan Table. The research tools included 1) a critical reading lesson plan using the SQ5R teaching method, 2) a test to measure critical reading abilities, and 3) a questionnaire to gather student opinions on SQ5R teaching method. Data analysis involved calculating means, standard deviations (S.D.), t - test dependent, and content analysis. The findings of the research indicate that 1) first - year students after teaching using the SQ5R teaching method was higher than before teaching, with statistical significance at the .01 level, and 2) The overall student opinions regarding the SQ5R teaching method were at the highest level of agreement, with an average score of 4.70. When considering each aspect, it was found that learning activities and the classroom environment were at the highest level for every item. Additionally, the benefits received were at the highest level, except for the fact that students practiced systematic thinking skills and gained new knowledge. This implies that in SQ5R teaching, questioning should be added as a major component and brought in as sub-data in order to better connect with the content of the story.